Teacher's Perception Of Student's Mathematics Learning Difficulties - Alfiah Nurfadhilah AM. Hindi; Isma Muthahharah (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
Difficulties in learning mathematics can be experienced by students with any level of ability from any circle or group. With the students' learning difficulties in mathematics, the question arises why this can happen and as educators, what is the teacher's perception of learning difficulties in mathematics. The purpose of this study was to describe Teacher's Perception of Students' Mathematics Learning Difficulties. This research used a descriptive qualitative approach with non-test data collection techniques through questionnaires and interviews. The results showed that: (i) the mathematics teacher's perception of the dominant causes of learning difficulties revealed psychological causes, including low interest or motivation and understanding of basic concepts as the cause of students' mathematics learning difficulties; (ii) the mathematics teacher's perception of the symptoms that are indicators of learning difficulties in mathematics, the most widely disclosed is the low ability of students to complete the tasks given by the teacher; (iii) the teacher's perception of the method used to investigate the existence of difficulties in learning mathematics, the most commonly done is through observation, interviews and documentation by looking at the results of tests or assignments of each student; (iv) the teacher's perception of examples of difficulties experienced by students in learning mathematics, which is widely revealed in the competency standard for understanding the properties of arithmetic operations and their use in problem solving being taught; and (v) teachers' perceptions of the efforts made to overcome students' mathematics learning difficulties vary according to their respective experiences. There are only a few teachers who do group guidance and individual guidance.